The Use of CIRC (Cooperative Integrated Reading and Composition) To Improve Students’ Reading on Recount Text - Riyanti, Novita; Sodiq, Jafar; Musarokah, Siti (Universitas Pahlawan Tuanku Tambusai, 2023)
The study is aimed to evaluate how well the Cooperative Integrated Reading and Composition (CIRC) method work as a framework for enhancing students’ reading skills of recount text at 8 grade of SMPN 37 Semarang. This study was conducted using a simple research method that compared the pre-test and post-test outcoes of 8 grade students at SMPN 37 Semarang, and was carried out in four stages; planning, acting, observing, and reflecting. The results and learning observations are among the outcomes of this study. The Cooperative Integrated Reading and Composition (CIRC) method was proven to be useful in enhancing students’ reading abilities based on the research’s findings. The test’s average score increased, and more pupils met the established criteria (KKM), according to the data. Pre test average are 71,90 and 62 % KKM achievement, and post-test averages are 84 and 85% KKM achievement. In addition, students also showed improvement in their reading ability and critical thinking, as seen in the learning observations by the teacher. Therefore, it can be concluded that the use of Cooperative Integrated Reading and Composition (CIRC) method can be an effective alternative way to improve students’ reading comprehension in recount text at 8 grade of SMPN 37 Semarang; it is recommended for English teachers to consider take of this strategy in teaching recount text at junior high school.